TERRESTRIAL MOLLUSKS OF THE HEIGHTS OF SIERRA MORENA IN CORRALILLO, VILLA CLARA, CUBA - Olivera Bacallao, Damaris (2017)
Th e investigation presents a malacological survey in heights of Sierra Morena, Corralillo, Villa Clara, Cuba. A total of 69 samples were collected from October 2015 until June 2016, georeferenced in a map (1:10000) and processed with numeric classifi cation techniques. A total of 26 species were identifi ed. Of the 26 species, one is endemic to the area and another is new to science. Established methodology was used for the collection of mollusks. Th ree species collected in the study area constitute potential vectors of organism pathogens to humans. It was possible to correlate the distribution of this species with the anthropogenic landscape, based on that information a potential protected area is proposed. Th e results of this study are useful to develop activities geared to environmental education.